Child Neurology (General Pediatric Neurology): Increased healthcare services utilization in the tuberous sclerosis complex population in Quebec. (3rd June 2015) - Bernier, A; Landry, JS; Kristof, AS; Carmant, L; Major, P
Abstract : Background: Tuberous sclerosis complex (TSC) is a neurocutaneous syndrome that can present with many disabling neurological symptoms, the most common being seizures. Although it is a chronic systemic syndrome, healthcare utilization and long-term outcome of subjects with TSC are not well defined. The goal of this study was to evaluate the direct cost and long-term outcome of TSC compared to other forms of epilepsy and healthy controls. Methods: Our provincial health care database was interrogated to determine use of medical services by patients with TSC, epilepsy and healthy controls from 1996-2011. Data on demographics, outcomes and health care utilization were analyzed. Results: 1004 TSC, 41, 934 with epilepsy and 41, 934 controls were identified. The prevalence of TSC was 1/7, 872 compared to 1/189 for epilepsy. TSC experienced more hospitalizations, medical visits and prescription drug use, resulting in higher total health care costs. Their most common admission diagnosis was seizures and age at death was significantly lower: 61, 3 years old for TSC vs 69, 6 and 76, 6 years old for epilepsy and controls, (p<0, 001). Conclusions: TSC subjects have a significantly higher burden of disease than other subjects with epilepsy. These results stress the need for specialized services in this population through the lifespan.